Remediation of the oil palm frond juice base medium via efficient pretreatment and dilution factor strategy for bacterial cellulose production yield enhancement - Shahril, Mohamad; Luqman Chuah, Abdullah; Saidatul Shima, Jamari; Sharifah Fathiyah, Sy Mohamad (Elsevier Ltd, 2025)
The presence of inhibitory components, especially lignin and weak acids in oil palm frond juice medium detrimentally affects bacterial cellulose production yield. This study investigated a two-stage pre-treatment and dilution strategy to enhance the suitability of oil palm frond juice. Pre-treatments for lignin removal included alkaline precipitation with 0.025 M sodium hydroxide, which reduced the lignin content by 73.5 %, and activated carbon adsorption at 6 % w/v, which achieve over 95.1 % lignin removal. Additional treatment procedure using dilution factors effectively mitigated the adverse effects of both pretreatment, including chemical residues, pH instability, and volume loss. Bacterial cellulose production in pre-treated oil palm frond juice with 40 % water dilution yielded at 2.35 g/L from alkaline pretreated medium and 2.57 g/L from activated carbon adsorption pretreated medium, representing a 7.0-fold and 3.6-fold increase over undiluted and untreated samples, respectively. These results demonstrate the effectiveness of lignin removal using alkaline precipitation or activated carbon adsorption with a dilution factor significantly improves the viability of oil palm frond juice as a high-yield bacterial cellulose production medium.